Strategic management in enhancing educational quality (environmental scanning done by the principal at SD N 01 Koto Tangah) - Zizvi Rilian Ramadona; Hanif Alkadri; Sufyarma M (International Conferences on Educational, Social Sciences and Technology)
In a school, principal has major contribution to lead better education. It could be assumed that a principal is the center of school policy in order to improve educational quality. Dealing with preceding explanation, a principal officially should conduct an environmental analysis in improving educational analysis. This paper presents the result of a study about environmental analysis conducted by principal of SD N 01 Koto Tangah. Data were obtained through interview, observation and documentation. The respondents were principal, school committee, teachers, and students’ parents. This paper revealed that there principal as the top leader of the school has done environmental analysis professionally. Principal involved school committee and society in shaping school vision, mission and school policy. There are two environments namely external and internal. Both of them have been analyzed by principal in order to improve educational quality particularly at SD N 01 Koto Tangah.